2020
DOI: 10.5114/aic.2020.99264
|View full text |Cite
|
Sign up to set email alerts
|

Endocan expression correlated with total volume of coronary artery dilation in patients with coronary artery ectasia

Abstract: Introduction: Inflammation and angiogenesis disturbances are considered as factors contributing to the development of coronary artery ectasias (CAE). Endocan (endothelial cell-specific molecule-1-ESM-1) regulates both inflammatory and angiogenetic processes. However, there are no data about the correlation between endocan level and the severity of CAE measured with total volume of coronary artery dilation. Aim: To assess whether the severity of the inflammatory process measured as endocan concentration correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A previous study showed that the total aneurysm volume was positively correlated with endocan (endothelial cell-specific molecule-1—ESM-1) concentration. ESM-1 regulates both inflammatory and angiogenetic processes, being a potential marker of vascular wall damage resulting from inflammation and vascular remodeling as a result of a disturbance of pro and antiangiogenic processes [ 11 ]. Angiogenesis is also regulated by molecular mechanisms [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the total aneurysm volume was positively correlated with endocan (endothelial cell-specific molecule-1—ESM-1) concentration. ESM-1 regulates both inflammatory and angiogenetic processes, being a potential marker of vascular wall damage resulting from inflammation and vascular remodeling as a result of a disturbance of pro and antiangiogenic processes [ 11 ]. Angiogenesis is also regulated by molecular mechanisms [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse vascular remodeling is considered to be a possible mechanism of CAAD development. [13][14][15] Therefore, assuming that the processes mentioned above involve the entire vascular bed, coronary microcirculation remodeling is thought to be a possible cause of CMD in CAAD patients. Moreover, a turbulent blood flow in aneurysms supports the development of thrombi, which may result in distal embolization and thus impair coronary microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography angiography is today the #1 tool to obtain CAAE 3D characteristics [4]. CTA, however, it is not performed prior to CAG identification of CAAE but, rather, as a subsequent step in arbitrarily selected cases [9]. Importantly, CTA resolution is > 2-fold lower than that of CAG (≈ 0.5 vs. ≈ 0.2 mm) [6,7], and CTA is prone to gating-related (increased heart rate, arrhythmias) and calcifications-related artifacts [4].…”
mentioning
confidence: 99%
“…For these reasons it would be of interest to employ 3D reconstructions as a potential replacement of CTA verification or as a guidance to selective CTA use. This is one of the major issues of interest today [9,10]; thus CAAE 3D reconstruction against CTA in a larger series of patients is required to fully validate this method.…”
mentioning
confidence: 99%